Bułgarskie wybory z literatury polskiej (na materiale z prasy literackiej) / Bulgarian extracts from Polish literature (materials from literary press) - Likomanova, Iskra (Przekłady Literatur Słowiańskich, 2009)
The article surveys translated excerpts from Polish literature, which have appeared in the Bulgarian specialized literary press-both weeklies and monthlies. The selection of Polish writers is reviewed as an aesthetic choice of texts, as a traditional presence in the Bulgarian culture, and as representative for the Polish literature in Bulgaria. The socio-cultural selection of Polish subjects is being analyzed and also the way they are being rendered by the translators.